2020
DOI: 10.1111/febs.15320
|View full text |Cite
|
Sign up to set email alerts
|

Williams–Beuren syndrome‐related methyltransferase WBSCR27: cofactor binding and cleavage

Abstract: Williams-Beuren syndrome, characterized by numerous physiological and mental problems, is caused by the heterozygous deletion of chromosome region 7q11.23, which results in the disappearance of 26 protein-coding genes. Protein WBSCR27 is a product of one of these genes whose biological function has not yet been established and for which structural information has been absent until now. Using NMR, we investigated the structural and functional properties of murine WBSCR27. For protein in the apo form and in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…A very recent study revealed that METTL18 is a histidine methyltransferase that regulates translation in cancer cells 9 . In addition to cancer, mutations and copy number alterations in METTLs can cause multiple neurological and multisystemic disorders 10 , 11 . Thus, previous studies demonstrate that METTLs are important regulators of cellular processes, which, if derailed, may result in the development of a multitude of diseases and disorders, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study revealed that METTL18 is a histidine methyltransferase that regulates translation in cancer cells 9 . In addition to cancer, mutations and copy number alterations in METTLs can cause multiple neurological and multisystemic disorders 10 , 11 . Thus, previous studies demonstrate that METTLs are important regulators of cellular processes, which, if derailed, may result in the development of a multitude of diseases and disorders, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we found that both SAM and SAH strongly bind to WBSCR27 ( Mariasina et al, 2020 ). Relatively small changes in the chemical shifts of the signals of the residues in the binding site of these two ligands indicate that the structure of WBSCR27-SAM and WBSCR27-SAH complexes is similar ( Mariasina et al, 2020 ).…”
Section: Resultsmentioning
confidence: 68%
“…Earlier we reported the backbone and side chain signal assignments for the complex SAH-WBSCR27 (BMRB-27417, Mariasina et al, 2018 ) and for the apo form of the protein (BMRB-27578, Mariasina et al, 2020 ) and deposited these data in BioMagResBank ( https://bmrb.io ). This information was used to determine NMR restraints.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, biallelic frameshift variants in the rRNA m 6 A methyltransferase METTL5 cause intellectual disability and microcephaly 14 . Heterozygous deletion of chromosome region 7q11.23, which contains METTL27 (also known as WBSCR27), causes Williams-Beuren syndrome (WBS), a neurodevelopmental and multisystemic disease 15 . Thus, previous studies demonstrate that METTLs are important regulators of cellular processes, which if derailed, may result in the development of a multitude of disease and disorders, including cancer.…”
Section: Introductionmentioning
confidence: 99%